Fundamental Supermultiplet in Twelve Dimensions - Curtright, Thomas (Frontiers in Physics, 2018)
We discuss a set of local fields which provide the on-shell massless states expected for the fundamental linear representation of supersymmetry in twelve dimensions. We recover the states of the anticipated N = 16, S = 4, massless supermultiplet upon reduction to four dimensions. Using algebraic methods, we also construct ghost arrays which permit the covariant quantization of each of the gauge fields in the set.